Effect of BTN162b2 and CoronaVac boosters on humoral and cellular immunity of individuals previously fully vaccinated with CoronaVac against SARS‐CoV‐2: A longitudinal study. Issue 8 (2nd May 2022) - Kuloğlu, Zeynep Ece; El, Rojbin; Guney‐Esken, Gulen; Tok, Yeşim; Talay, Zeynep Gülçe; Barlas, Tayfun; Kuskucu, Mert Ahmet; Albayrak, Özgür; Doğan, Özlem; Yavuz, Serap Şimşek; Midilli, Kenan; Ergönül, Önder; et al.
Abstract: Background: It is essential to know about immune response levels after booster doses of the two different types of vaccines, mRNA, and the inactivated, currently used against COVID‐19. For this purpose, we aimed to determine the effects of BNT162b2 (BNT) and CoronaVac (CV) boosters on the humoral and cellular immunity of individuals who had two doses of CV vaccination. Methods: The study was conducted in three centers (Koc University Hospital, Istanbul University Cerrahpasa Hospital, and Istanbul University, Istanbul Medical School Hospital) in Istanbul, Turkey. Individuals who had been previously immunized with two doses of CV and no history of COVID‐19 were included. The baseline blood samples were collected 3–5 months after the second dose of CV. Follow‐up blood samples were taken 1 and 3 months after administration of third doses of CV, or one dose of BNT boosters. Neutralizing antibody titers were measured by plaque reduction assay. The CD4+ T cell, CD8+ T cell, effector CD4+CD38+CD69+ T cell, and effector CD8+CD38+CD69+ T cell ratios were determined by flow cytometry. The intracellular IFN‐γ and IL‐2 responses were measured by ELISpot assay. Results: We found a 3.38‐fold increase in neutralizing antibody geometric mean titers (NA GMT, 78.69) 1 month after BNT booster and maintained at the third month (NA GMT, 80). Nevertheless, in the CV booster group, significantly lower NA GMT than BNT after 1 month and 3 months were observed (21.44 and 28.44, respectively) ( p  < .001). In the ELISpot assay, IL‐2 levels after BNT were higher than baseline and CV booster ( p  < .001) while IFN‐γ levels were significantly higher than baseline ( p  < .001). The CD8+CD38+CD69+ and CD4+CD38+CD69+ T cells were stimulated predominantly in the third month of the BNT boosters. Conclusion: The neutralizing antibody levels after 3 months of the BNT booster were higher than the antibody levels after CV in fully vaccinated individuals. On the contrary, ratio of the effector T cells increased along with greater IFN‐γ activation after BNT booster. By considering the waning immunity, we suggest a new booster dose with BNT for the countries that already had two doses of primary CV regimens. Abstract : This study determines the effects of BNT162b2 (BNT) and CoronaVac (CV) boosters on the humoral and cellular immunity of individuals who had two doses of CV vaccination. The neutralizing antibody levels after 3 months of the BNT booster are higher than the antibody levels after CV in fully vaccinated individuals. The ratio of the effector T cells increases along with greater IFN‐γ activation after BNT booster.Abbreviations: GMT, geometric mean titer; PBMCs, peripheral blood mononuclear cells; PRNT50, plaque reduction neutralization test; SFU, spot‐forming units